Method for making silicon nitride ceramic substrate with copper plate
A two-step sintering process and vacuum welding method enhance silicon nitride ceramic substrates with copper plates, addressing thermal conductivity and stability issues, enabling their use in high-power semiconductor devices.
Patent Information
- Application Number
- JP2023543222
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-01-20
- Filing Date
- 2022-01-17
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2042-01-17
AI Technical Summary
Conventional silicon nitride ceramic materials have thermal conductivity that cannot meet the heat dissipation demands of high-power semiconductor devices, and their sintering process is hindered by low sintering aid content leading to densification issues, while existing ceramic substrates with copper plates face stability problems with thicker copper foils.
A two-step sintering process with controlled grain boundary phase composition and a low oxygen content, combined with a vacuum welding method using a solder foil piece, to create a silicon nitride ceramic substrate with a copper plate, ensuring high thermal conductivity and stability.
The method produces a silicon nitride ceramic substrate with copper plates that exhibits high thermal conductivity, improved breakdown electric field strength, and resistance to thermal shock, suitable for high-power semiconductor devices.
Smart Images

Figure 0007617290000001 
Figure 0007617290000002 
Figure 0007617290000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a silicon nitride ceramic substrate with a copper plate, and belongs to the field of semiconductor materials and devices. [Background technology]
[0002] In recent years, semiconductor devices have been rapidly developing toward higher power, higher frequency, and greater integration. The heat generated by the operation of semiconductor devices is a factor that can cause failures in semiconductor devices, and the thermal conductivity of insulating substrates is an important factor that affects the overall heat dissipation of semiconductor devices. In addition, in fields such as electric vehicles, high-speed railways, and rail traffic, semiconductor devices are constantly exposed to complex mechanical environments, including shocks and vibrations, during use, which places strict demands on the reliability of the materials used.
[0003] High thermal conductivity silicon nitride (Si3N4) ceramics is considered to be the optimal semiconductor insulating substrate material with high strength and high thermal conductivity due to its excellent mechanical and thermal performance, and has great potential in the heat dissipation application of high power insulated gate bipolar transistors (IGBTs). The theoretical thermal conductivity of silicon nitride crystal is 400 W m -1 ·K -1 With its excellent mechanical properties and potential for high thermal conductivity, silicon nitride ceramics are expected to make up for the shortcomings of existing ceramic substrate materials such as alumina and aluminum nitride, and have great potential for application to high-end semiconductor devices, especially high-power IGBT heat dissipation substrates. However, the thermal conductivity of conventional silicon nitride ceramic materials is only 20-30 W·m -1 ·K -1 However, the application demand for heat dissipation of high-power semiconductor device substrates cannot be met at all.
[0004] On the other hand, silicon nitride is a strong covalent compound and is difficult to sinter densely by solid-state diffusion, so it is necessary to add an appropriate amount (the amount added is usually more than 5wt%) of rare earth oxides and / or metal oxides as sintering aids (e.g. Y2O3, La2O3, MgO, Al2O3, CaO, etc.). However, the addition of sintering aids significantly reduces the thermal conductivity of silicon nitride ceramics, and a low content of sintering aids contributes to obtaining high thermal conductivity, but a low content of sintering aids leads to problems with densification of silicon nitride ceramics sintering.
[0005] With the development of power devices (including LED, LD, IGBT, CPV, etc.), heat dissipation has become a key technology that affects device performance and stability. For electronic devices, every 10°C increase in temperature usually reduces the effective life of the device by 30% to 50%. Therefore, the selection of appropriate packaging materials and processes and the improvement of device heat dissipation capabilities have become technical bottlenecks in the development of power devices.
[0006] The ceramic substrate is also called ceramic circuit board, and includes ceramic substrate and metal wiring layer. For electronic packaging, packaging substrate plays an important role of connecting internal and external heat dissipation channels as an intermediate body, and also has the functions of electrical interconnection and mechanical support. Silicon nitride ceramics has advantages such as high thermal conductivity, good heat resistance, high mechanical strength, and low thermal expansion coefficient, and is a preferred substrate material for packaging power semiconductor devices. Here, the ceramic substrate with copper plate is an important component of high-power devices, and has the characteristics of high thermal conductivity, high electrical insulation, high mechanical strength, low expansion, etc. of ceramics, and combines the high conductivity and excellent solderability of oxygen-free copper, and can be etched with various graphics like polymer substrate PCB circuit board.
[0007] According to the requirements of packaging structure and application, ceramic substrates can be divided into two kinds: planar ceramic substrates and three-dimensional ceramic substrates. According to the fabrication principle and process, planar ceramic substrates can be divided into thin-film ceramic substrates, thick-film printed ceramic substrates, direct-bonded copper ceramic substrates, active metal brazing ceramic substrates, direct electroplating copper ceramic substrates, and laser-activated cermet substrates. Among them, as active metal brazing ceramic substrates (active metal bonding method, Active Metal Brazing, AMB), AMB ceramic substrates realize the welding between copper foil and ceramic substrates by solder containing a small amount of active metal elements. AMB substrates realize the bonding by relying on the chemical reaction occurring between active solder and ceramic interface, so they have unique advantages such as high bonding strength, strong high and low temperature impact failure resistance, and high stability, and have become the preferred packaging material for new generation semiconductors and new high-power electronic devices.
[0008] The AMB welding process of ceramic substrate and copper foil involves first coating the surface of the ceramic substrate with an active metal solder layer, then heating under vacuum conditions to create a chemical bond between the active metal element and the surface element of the ceramic substrate, thus achieving a high-strength connection between the two. The methods for coating the solder layer on the substrate surface mainly include screen printing, plating, sputtering, spraying, etc., and different processes have their own characteristics. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] China Patent Application Publication No. 104409425 [Patent Document 2] China Patent Publication No. 1597614 [Patent Document 3] China Patent Application Publication No. 108585881 [Patent Document 4] China Patent Publication No. 108383532 [Patent Document 5] European Patent Application Publication No. 3156366 [Patent Document 6] JP 2002-293641 A Summary of the Invention
[0010] SUMMARY OF THE PRESENT EMBODIMENTS In view of the above problems, an object of the present invention is to provide a silicon nitride ceramic substrate with a copper plate and a method for producing the same.
[0011] In one aspect, the present invention provides a method for producing a silicon nitride ceramic substrate with a copper plate. The method for producing a silicon nitride ceramic substrate of the present invention comprises a silicon nitride ceramic substrate with a copper plate, copper plates disposed on both the upper and lower sides of the silicon nitride ceramic substrate, and a welding layer disposed between the copper plate and the silicon nitride ceramic substrate, the silicon nitride ceramic substrate contains a silicon nitride phase and a grain boundary phase as components, the content of the silicon nitride phase is ≧95wt%, the grain boundary phase is a mixture containing at least three elements Y, Mg, and O, the components and contents of the grain boundary phase are adjusted by a two-stage sintering process to make the content of the grain boundary phase ≦5wt% and the content of the crystal phase in the grain boundary phase ≧40vol%, and the sintering aids used in the production of the silicon nitride ceramic substrate are Y2O3 and MgO, and the molar ratio of the two is 1.0-1.4:2. the thickness of the silicon nitride ceramic substrate is 0.2-2.0 mm; the composition of the welding layer is AgCuTi, where the mass ratio of Ag:Cu:Ti is x:y:z, where x=0.60-0.65, y=0.33-0.37, z=0.01-0.04, and x+y+z=1; the thickness of the welding layer is 20-60 microns; the thickness of the copper plate is 0.1-1.5 mm; according to the structure of the silicon nitride ceramic substrate with the copper plate, the copper plate, the solder foil piece formed as the welding layer, and the silicon nitride ceramic substrate are laminated, and then sintered in a protective atmosphere. Debindingand then vacuum welding the copper plate and the copper-plated silicon nitride ceramic substrate while maintaining the temperature at 860 to 920° C. for 5 to 20 minutes to obtain the copper plate-attached silicon nitride ceramic substrate.
[0012] Preferably, the total amount of impurities in the silicon nitride ceramic material is ≦1.0 wt %, and the impurities include at least one of lattice oxygen, metal impurity ions, and impurity carbon.
[0013] Preferably, the copper plate has a thickness of 0.2 mm to 1.0 mm.
[0014] Preferably, the silver powder has an average particle size of 5 to 20 μm and an oxygen content of 0.05% or less, the copper powder has an average particle size of 5 to 20 μm and an oxygen content of 0.05% or less, the titanium powder has an average particle size of 1 to 5 μm and an oxygen content of 0.2% or less, and the protective atmosphere is a nitrogen atmosphere.
[0015] Preferably, the cast film blank is dried using a flowing heat N2 atmosphere with an increasing temperature, the temperature range of the N2 atmosphere is 40-85°C, and the atmospheric pressure is 0.1-0.2MPa. Preferably, the nitrogen atmosphere has two temperature stages, the atmospheric temperature range of the previous stage is 40-65°C, and the atmospheric temperature range of the subsequent stage is 60-85°C, and the atmospheric temperature of the previous stage is less than the atmospheric temperature of the subsequent stage.
[0016] Preferably, Debinding The parameters are the pressure of the N2 atmosphere of 0.1 to 0.2 MPa, the treatment temperature of 500 to 800° C., and the treatment time of 1 to 3 hours.
[0017] Preferably, the method for producing the silicon nitride ceramic substrate includes the steps of: (1) mixing at least one of silica fume and silicon nitride powder as raw material powder, Y2O3 powder and MgO powder as sintering aids, and an organic solvent and adhesive in a protective atmosphere to obtain a mixed slurry; and (2) tape-casting the mixed slurry in a protective atmosphere to obtain a base material. The method includes step (3) of placing the obtained raw material in a reducing atmosphere and performing a pretreatment at 500-800°C to obtain a rough body, and step (4) of placing the obtained rough body in a nitrogen atmosphere and first performing a low-temperature heat treatment at 1600-1800°C and then a high-temperature heat treatment at 1800-2000°C to obtain the silicon nitride ceramic substrate, wherein preferably the protective atmosphere is an inert atmosphere or a nitrogen atmosphere, and preferably a nitrogen atmosphere, and the reducing atmosphere is a hydrogen-nitrogen mixed atmosphere having a hydrogen content of 5 vol% or less.
[0018] Preferably, the method for producing the silicon nitride ceramic substrate includes the steps of: (1) mixing and shaping at least one of silica fume and silicon nitride powder as raw material powder, and Y2O3 powder and MgO powder as sintering aids in a protective atmosphere to obtain a raw material; (2) placing the raw material in a reducing atmosphere and performing pretreatment at 500-800°C to obtain a rough body; and (3) placing the rough body in a nitrogen atmosphere and first performing low-temperature heat treatment at 1600-1800°C and then high-temperature heat treatment at 1800-2000°C to obtain the silicon nitride ceramic substrate. Preferably, the protective atmosphere is an inert atmosphere or a nitrogen atmosphere, and is preferably a nitrogen atmosphere, and the reducing atmosphere is a hydrogen-nitrogen mixed atmosphere having a hydrogen content of 5 vol% or less. Effect of the Invention
[0019] In the present invention, the amount of structural defects such as crystal vacancies and dislocations is reduced by controlling the oxygen content during the preparation process (including avoiding oxidation of raw materials during mixing and forming the dough, and pre-treatment in a reducing atmosphere), controlling the content of metal impurity ions, and controlling the carbon content, thereby achieving the purpose of improving the thermal conductivity and breakdown field strength of silicon nitride ceramic materials. At the same time, the components and contents of the grain boundary phase are adjusted by a two-stage sintering process, so that the sintering aids are promoted to generate a liquid phase in the low-temperature sintering stage, promoting densification, and the remaining MgO sintering aids are volatilized in the high-temperature stage, while the content of the glass phase in the grain boundary phase is further reduced, thereby achieving the purpose of reducing the content of the grain boundary phase, increasing the crystallization degree of the grain boundary phase, and further improving the thermal conductivity. At the same time, the high breakdown field strength of the material contributes to the application in high-power devices, and contributes to reducing the thickness of the substrate material and reducing the thermal resistance, and the coated copper plate made using this material exhibits the typical properties of thermal shock resistance, high reliability, and long life. In the present invention, after the active metal powder is mixed uniformly, the solder foil strip is formed by tape casting, which ensures uniform distribution and thickness consistency of each component in the solder, and protects the solder by using an inert atmosphere during the solder mixing and forming process to avoid oxidation of the metal powder, and ensures high-strength welding of the silicon nitride ceramic substrate with copper plate. At the same time, the solder foil strip is formed to achieve uniform coating on the ceramic substrate surface, which avoids the uneven solder phenomenon that is easily caused by the traditional screen printing process, and achieves low-stress welding of the silicon nitride ceramic substrate with copper plate, and the metal solder layer is uniformly distributed between the ceramic substrate and the copper plate, which prevents soldering errors and improves reliability. In addition, the ceramic substrate with copper plate made from the conventional aluminum nitride, alumina, and zirconia-reinforced alumina (ZTA) ceramic substrate can only be welded to thin copper foil (generally less than 0.8 mm). If the copper foil is too thick, the stability will be reduced sharply.On the other hand, the method of the present invention is applicable to welding of high thermal conductive ceramic substrates and thick copper foils (0.1 to 1.5 mm), and even for copper foils with a thickness of 1 mm or more, a silicon nitride ceramic substrate with a copper plate can still be produced that has high strength, low stress, and high stability. However, thick copper foils can withstand a larger current density and are applicable to higher power semiconductor devices. [Brief description of the drawings]
[0020] [Figure 1] 1 is an XRD pattern of the silicon nitride ceramic material produced in Example 1. [Diagram 2] 1 is a typical SEM microstructure of the silicon nitride ceramic material produced in Example 1. [Diagram 3] 1 is a typical TEM microstructure of the silicon nitride ceramic material produced in Example 1. [Figure 4] 1 is an XRD pattern of the material produced after nitridation in Example 6. [Diagram 5] 1 is an XRD pattern of the material produced in Example 6 after high temperature sintering. [Figure 6] 1 is a typical SEM microstructure of the silicon nitride ceramic material produced in Example 6. [Figure 7] 1 is a diagram of the active metal solder foil strip produced according to the present invention. [Figure 8] FIG. 2 is a schematic diagram of the structure of a silicon nitride ceramic substrate with a copper plate. [Figure 9] This is a silicon nitride ceramic substrate with a copper plate produced in Example 12. [Figure 10] 1 is a microstructure of the welded area of a silicon nitride ceramic substrate with a copper plate. [Figure 11] The microstructure of the welded area of the silicon nitride ceramic substrate with copper plate (a) and its composition analysis (b). [Figure 12] This is an ultrasonic scan map of a silicon nitride ceramic substrate with a copper plate after high-temperature and low-temperature cycle thermal shock. [Figure 13] Table 1 shows the composition of silicon nitride ceramic materials and their manufacturing process. [Figure 14] Table 2 shows the phase composition and performance parameters of silicon nitride ceramic materials. [Figure 15] Table 3 shows the composition of the solder foil pieces produced according to the present invention. [Figure 16] Table 4 shows the manufacturing parameters and performance parameters of the silicon nitride ceramic substrate with a copper plate in the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] The present invention will be further described below with reference to the following embodiments. It should be understood that the following embodiments are only for illustrating the present invention, and are not intended to limit the present invention.
[0022] In the present disclosure, the silicon nitride ceramic material contains 95% or more of silicon nitride phase and a grain boundary phase with a crystalline phase content of 40% or more. The silicon nitride ceramic material thus obtained has low contents of lattice oxygen, metal impurity ions, carbon impurities, etc., with the total amount being 1.0 wt% or less. Therefore, the silicon nitride ceramic material in the present invention has high thermal conductivity and breakdown electric field strength.
[0023] In one embodiment of the present invention, a cleaning and protective atmosphere preparation process is adopted to avoid contact of air or hot air with the material, and the impurity content and oxygen content in the ceramic preparation are controlled, so that the thermal conductivity and breakdown field strength of the material are improved without reducing the bending strength of the material. The method for preparing silicon nitride ceramic material provided by the present invention is described below by way of example.
[0024] The method for preparing the silicon nitride ceramic material specifically includes the steps of mixing and green compacting in a protective atmosphere, pre-treatment in a reducing atmosphere, sintering in a nitrogen atmosphere, and sintering precision control.
[0025] Mixing in a Protective Atmosphere The raw material powder, sintering aid Y2O3 powder and MgO powder are mixed uniformly in a sealed container with anhydrous ethanol as a solvent, protected in a protective atmosphere, and then dried to obtain a mixed powder. Alternatively, the raw material powder, sintering aid Y2O3 powder and MgO powder are placed in a sealed container, and anhydrous ethanol as an organic solvent and PVB as an adhesive are added, and then the mixture is mixed uniformly in a protective atmosphere to obtain a mixed slurry. The adhesive may be 5-9wt% of the total mass of the raw material powder + sintering aid. The intrinsic content of the obtained mixed slurry is 50-70wt%.
[0026] In an alternative embodiment, the protective atmosphere used for mixing is an inert atmosphere or a nitrogen atmosphere, preferably a nitrogen atmosphere. Preferably, mixing is performed using a closed container with a polyurethane or nylon lining, and the container is sparged with nitrogen to prevent air ingress.
[0027] In an alternative embodiment, the raw powder is silicon nitride powder, silica fume, or a mixed powder of silicon nitride powder and silica fume, in which the mass ratio of silica fume in the mixed powder of silicon nitride and silicon is 75% or more, that is, the mass ratio of silicon nitride generated after the Si powder nitriding process to the total silicon nitride phase is 80% or more.
[0028] In an alternative embodiment, the total mass of the sintering aid (Y2O3 powder and MgO powder) is 5 wt% or less of the total mass of the raw material powder + sintering aid. If the amount of sintering aid is too much, the grain boundary phase content in the silicon nitride ceramic material produced increases, so the thermal conductivity and breakdown field strength of the material decrease. If the amount of sintering aid is too little, densification cannot be sufficiently promoted, the density of the silicon nitride ceramic material produced is relatively low, the porosity increases, and the thermal conductivity and breakdown field strength of the material decrease. More preferably, the molar ratio of Y2O3 and MgO in the sintering aid may be 1.0-1.4:2.5-2.9. If MgO is excessive, the liquid phase eutectic temperature formed by the sintering aid is relatively low, and MgO volatilizes seriously at high temperatures, so the thermal conductivity and breakdown field strength of the silicon nitride ceramic material produced are relatively low. If the amount of MgO is small, the proportion of MgO in the sintering aid is relatively low, so the liquid phase eutectic temperature formed by the sintering aid is relatively high and the effect of densifying the material is relatively poor, so that the thermal conductivity and breakdown field strength of the prepared silicon nitride ceramic material are both significantly reduced.
[0029] Dough forming in a protective atmosphere In a protective atmosphere, the mixed powder is directly press molded to obtain a dough. Here, the press molding method includes, but is not limited to, dry press molding, isostatic compression molding, etc. Alternatively, in a protective atmosphere, the mixed slurry is directly tape cast molded to obtain a dough (flake dough). Preferably, the mixed slurry is vacuum degassed before tape casting (the vacuum degree is generally -0.1 to -10 kPa, and the treatment time is 4 to 24 hours). More preferably, the scraper height of the tape casting molding is controlled to adjust the thickness of the flake dough. In an optional embodiment, the protective atmosphere used for dough molding may be an inert atmosphere or a nitrogen atmosphere, and is preferably a nitrogen atmosphere. Generally, nitrogen is directly injected during molding to provide protection.
[0030] Pretreatment of the molding material in a reducing atmosphere The pretreatment of the molding mixture is carried out at a constant temperature in a reducing atmosphere to remove oxygen from the raw powder and to remove organic matter from the molding mixture. In an alternative embodiment, when the raw powder is silica fume or a mixed powder of silicon nitride and silicon, the molding mixture is first pretreated at a constant temperature in a reducing atmosphere, and then further nitrided in a reducing atmosphere.
[0031] In an alternative embodiment, the pretreatment may be performed in a reducing nitrogen atmosphere having a hydrogen content of 5% or less, and the gas pressure of the reducing atmosphere is 0.1 to 0.2 MPa. The pretreatment temperature may be 500 to 800°C, and the heat retention time may be 1 to 3 hours.
[0032] In an alternative embodiment, the nitriding treatment may be performed in a nitrogen atmosphere having a hydrogen content of 5% or less, and the atmospheric pressure is 0.1 to 0.2 MPa. The nitriding treatment temperature is 1350 to 1450° C., and the heat retention time is 3 to 6 hours.
[0033] The sintering process of the rough body includes low-temperature heat treatment and high-temperature heat treatment. Specifically, the sintering process is densified by a stepwise sintering process under high nitrogen pressure, and the stepwise sintering process includes low-temperature heat treatment to suppress the volatilization of low-melting-point substances in the sintering aid, and further high-temperature sintering to densify it. In the present invention, the sintering process should adopt gas pressure sintering under high nitrogen pressure conditions, and the atmospheric pressure may be 0.5-10 MPa. The rough body can be sintered in a BN crucible. Here, the temperature of the low-temperature heat treatment (low-temperature sintering) may be 1600-1800°C, and the warming time may be 1.5-2.5 hours. The temperature of the high-temperature heat treatment (high-temperature sintering) may be 1800-2000°C, and the warming time may be 4-12 hours.
[0034] In the present invention, the silicon nitride ceramics produced have low contents of lattice oxygen, metal impurity ions, impurity carbon, etc., and are characterized by high thermal conductivity and high breakdown electric field strength. The thermal conductivity is 90 W m -1 ·K -1 At the same time, the breakdown electric field strength is 30KV / mm or more.
[0035] In the present disclosure, a silicon nitride ceramic substrate with a copper plate is prepared using an active metal brazing process, and the steps of mixing the solder, forming the solder foil blanks, cutting and stacking the solder foil blanks, and stacking the laminated pieces are performed. Debinding and vacuum welding of silicon nitride-coated copper plates, etc. The method for producing the silicon nitride ceramic substrate with a copper plate provided by the present invention will now be described by way of example.
[0036] Solder Mixing In a sealed container and under N2 atmosphere protection, the silver powder, copper powder, titanium powder, organic solvent and adhesive are mixed uniformly to obtain a mixed slurry. Specifically, the mixture is mixed by wet ball milling using a sealed container, and an N2 atmosphere of 0.1 MPa is injected into the container to prevent air from entering. Here, the silver powder may have a mass percentage of 60-65%, an average particle size of 5-20 μm, and an oxygen content of 0.05% or less, the copper powder may have a mass percentage of 33-37%, an average particle size of 5-20 μm, and an oxygen content of 0.05% or less, and the titanium powder may have a mass percentage of 1-4%, an average particle size of 1-5 μm, and an oxygen content of 0.2% or less. In an alternative embodiment, the adhesive may be polyvinyl butyral (PVB), and the amount of the adhesive added may be 5-15 wt% of the total mass of the silver powder, copper powder and titanium powder. Preferably, the slurry further contains at least one of other auxiliaries, such as an antifoaming agent, a dispersing agent, and a plasticizer. The antifoaming agent may be oleic acid, and the amount added may be 0.2 to 1.0 wt% of the total mass of the silver powder, the copper powder, and the titanium powder. The dispersing agent may be at least one of polyethylene glycol (PEG) and triethyl phosphate (TEP), and the amount added may be 0.2 to 1.0 wt% of the total mass of the silver powder, the copper powder, and the titanium powder. The plasticizer may be at least one of diethyl phthalate (DEP), dibutyl phthalate (DBP), and polyethylene glycol (PEG), and the amount added may be 2 to 6 wt% of the total mass of the silver powder, the copper powder, and the titanium powder. The intrinsic content of the mixed solder slurry may be 55 to 75 wt%.
[0037] Molding of solder foil pieces The mixed slurry is tape-cast in a N2 atmosphere and dried in a hot N2 atmosphere to produce a solder foil blank with a uniform thickness. The thickness of the formed solder foil blank is 20-60 μm, with a thickness deviation of ±10 μm or less.
[0038] In an alternative embodiment, the cast film fabric is dried using a flowing hot N2 atmosphere with increasing temperature. The temperature range of the hot N2 atmosphere is 40-85°C, and the pressure of the atmosphere is 0.1-0.2MPa. In the flowing hot N2 atmosphere with increasing temperature, the atmosphere temperature range is 40-65°C in the front stage and 60-85°C in the rear stage.
[0039] Cutting and stacking of solder foil strips The dried solder foil is cut into foil pieces that match the size of the silicon nitride ceramic substrate, and the silicon nitride ceramic substrate, the solder foil, and the copper foil are laminated. Here, the solder foil is laminated by placing one solder foil piece on each of the top and bottom surfaces of the silicon nitride substrate, and then placing one layer of copper foil of the same size on the outside of the solder foil piece.
[0040] Laminated Pieces Debinding The laminate is heat-treated under a constant temperature condition with a slight positive pressure. Debinding A slight positive pressure is generated by injecting a N2 atmosphere, the atmospheric pressure is 0.1 to 0.2 MPa, the treatment temperature is 500 to 800°C, and the treatment time is 1 to 3 hours.
[0041] Vacuum welding of silicon nitride coated copper sheets The laminated pieces are vacuum welded under a constant temperature condition in a vacuum. The vacuum welding parameters are: vacuum degree 10 -2 ~10 -4 Pa, welding temperature is 860 to 920°C, and heat retention time is 5 to 20 minutes.
[0042] In the present invention, the silicon nitride ceramic material may be made into a coated copper plate, which may then be used as a heat dissipation substrate for a high-power insulated gate bipolar transistor (IGBT) module. The coated copper plate made from the obtained silicon nitride ceramic has characteristics such as thermal shock resistance, high reliability, and long service life.
[0043] The present invention will be described in detail below with reference to examples. Similarly, the following examples are only used to further explain the present invention and should not be understood as limiting the scope of protection of the present invention. Any essential improvements and adjustments made by those skilled in the art based on the above content of the present invention are within the scope of protection of the present invention. The following exemplary process parameters are also examples of appropriate ranges. In other words, those skilled in the art can make selections within appropriate ranges based on the description in this specification, and are not limited to the following exemplary specific values.
[0044] Example 1 First, 95g of Si3N4, 5g of sintering aid powder (Y2O3:MgO=1.2:2.5, molar ratio), 1g of castor oil, 1g of PEG, 70g of anhydrous ethanol and 200g of silicon nitride polishing balls were placed in a polyurethane-lined ball mill tank with atmosphere protection function. After packaging the ball mill tank cap, the tank was vacuumed in order, N2 protective atmosphere was injected, and a slurry was obtained after 6 hours of ball milling mixing. 5g of PVB and 3g of DBP were further added to the above slurry, followed by 6 hours of ball milling under N2 atmosphere protection to obtain a uniform slurry. Next, the slurry was vacuum degassed for 6 hours, and the substrate was tape-cast under N2 atmosphere protection. The thickness of the substrate was d±0.05mm (d=0.2~2.0). Again, the green substrate was cut into the required shape and placed in a BN crucible and placed in a carbon tube furnace, after which heat treatment was carried out in the following process sequence: (1) In a 0.15 MPa N2 (containing 5% H2) atmosphere, heat to 600°C at a rate of 5°C / min and then leave for 2 hours. Debinding Pre-processing is carried out, (2) In a 2 MPa N2 atmosphere, the temperature was raised to 1650°C at a rate of 5°C / min, and then low-temperature heat treatment was performed for 2 hours. (3) In an 8MPa N2 atmosphere, the temperature was raised to 1950°C at a rate of 3°C / min, and then sintered at high temperature for 8 hours. (4) Cool in the furnace to room temperature.
[0045] The silicon nitride ceramic substrate material produced in this Example 1 has a bending strength of 810 MPa and a thermal conductivity of 106 W m -1 ·K -1 The breakdown field strength was 45KV / mm. The XRD pattern of this material, as shown in Figure 1, only had high intensity β-Si3N4 diffraction peaks, and no obvious steamed bread-shaped peaks. This indicates that the content of β-Si3N4 phase in the fabricated material was greater than 95wt%, and the content of grain boundary phase was less than 5%. The typical SEM microstructure of the material, as shown in Figure 2, showed that the material had high density and uniform microstructure. The Si3N4 grains (gray black areas) exhibited a typical bimodal distribution, and were composed of fine equiaxed Si3N4 grains and large long columnar Si3N4 grains interdigitated with each other. The content of grain boundary phase (gray area) was low, and was uniformly diffused and distributed in the Si3N4 matrix. Furthermore, statistical analysis from at least 10 SEM images and reference to the total amount of sintering aids in the raw materials ≦5wt% confirmed that the content of grain boundary phase in the silicon nitride ceramic material prepared in this example was less than 5%. A typical TEM microstructure of the material is shown in Figure 3 (B in Figure 3 is a partial enlargement of the dotted box area in A in Figure 3), in which the grain boundary phase (gray area) is dispersedly distributed between the Si3N4 crystal grains (gray black area), but the grain boundary phase is composed of a glass phase (light area) and a crystalline phase (dark area). As a result of statistical analysis from at least 10 TEM images, the content of the crystalline phase in the grain boundary phase of the silicon nitride ceramic material prepared in this example was about 54 vol%.
[0046] Examples 2 to 5 Specific parameters such as raw material composition, sintering aid composition, pretreatment process, and sintering process are shown in Table 1 (FIG. 13). The process steps refer to Example 1, and the composition and performance of the produced material are shown in Table 2 (FIG. 14).
[0047] Example 6 First, 3g of Si3N4 powder, 55g of Si powder, 4.5g of sintering aid powder (Y2O3:MgO=1.4:2.6, molar ratio), 0.7g of castor oil, 0.6g of PEG, 50g of anhydrous ethanol and 130g of silicon nitride grinding balls were placed in a ball mill tank with polyurethane lining and atmospheric protection. After packaging the ball mill tank cap, the tank was vacuumed and N2 protective atmosphere was injected, and the slurry was obtained after 8 hours of ball milling mixing. 4g of PVB and 2.5g of DBP were further added to the above slurry, followed by 6 hours of ball milling under N2 atmosphere protection, and a uniform slurry was obtained. Next, the slurry was vacuum degassed for 6 hours, and the substrate fabric was tape-cast under N2 atmosphere protection. Again, the molded substrate fabric was cut into the required shape and placed in a BN crucible and placed in a carbon tube furnace, and then heat-treated in the following process sequence: (1) In a 0.2 MPa N2 (containing 5% H2) atmosphere, heat the sample to 600°C at a rate of 4°C / min and then store for 3 hours. Debinding Pre-processing is carried out, (2) The specimen was heated to 1450°C at a rate of 5°C / min under a 0.2MPa N2 (5% H2) atmosphere, and then nitrided for 6 hours. (3) The specimen was heated to 1700°C at a rate of 6°C / min under a 3MPa N2 atmosphere, and then subjected to low-temperature heat treatment for 2 hours. (4) In an 8MPa N2 atmosphere, the temperature was raised to 1950°C at a rate of 5°C / min, and then sintered at high temperature for 10 hours. (5) Cool in the furnace to room temperature.
[0048] The silicon nitride ceramic substrate material produced in this Example 6 has a bending strength of 710 MPa and a thermal conductivity of 110 W m -1 ·K -1The breakdown electric field strength was 48KV / mm. The XRD pattern of this material after the nitriding process (above process (2)) is shown in FIG. 4, which shows that the main crystal phase is α-Si3N4 and contains a small amount of β-Si3N4 phase (5-10%). The XRD pattern of this material after the high-temperature sintering process (above process (4)) is shown in FIG. 5, which shows that only β-Si3N4 diffraction peaks exist, and there is no obvious steamed bread peak. This indicates that the content of β-Si3N4 phase in the fabricated material is greater than 95wt%, and the content of grain boundary phase is less than 5wt%. Furthermore, using the same method as in Example 1 above, it was measured that the content of crystalline phase in the grain boundary phase of the fabricated material was about 60vol%. The typical SEM microstructure of the material cut surface is shown in FIG. 6, which shows that the material has a high density, a uniform microstructure, and is composed of small and fine equiaxed Si3N4 crystal grains and large and long columnar Si3N4 crystal grains interdigitated with each other.
[0049] Examples 7 to 10 Specific parameters such as raw material composition, sintering aid composition, pretreatment process, nitriding process, sintering process, etc. are shown in Table 1 (Fig. 13). The process steps refer to Example 6, and the produced material composition and performance are shown in Table 2 (Fig. 14).
[0050] Example 11 In this Example 11, the preparation process of silicon nitride ceramic material is referred to Example 1, and the main difference is that 95g of Si3N4 powder, 5g of sintering aid powder (Y2O3:MgO=1.2:2.5, molar ratio), 1g of castor oil, 1g of PEG, 70g of anhydrous ethanol and 200g of silicon nitride grinding balls were placed in a ball mill tank with polyurethane lining and atmospheric protection function. After packaging the ball mill tank cap, the tank was vacuumed, N2 protective atmosphere was injected, and ball milled for 6 hours to obtain a slurry. Then, the mixture was dried, sieved, dry press molded (20 MPa) and cold isostatically pressed (200 MPa) in a nitrogen atmosphere to obtain a dough.
[0051] Comparative Example 1 The specific parameters of raw material formulation, sintering aid composition, pretreatment process, sintering process, etc. are the same as those of Example 1 (see Table 1 (Figure 13)), and the process steps refer to Example 1, with the difference being that no nitrogen atmosphere protection measures are adopted during the processes of ball mill mixing and dough molding. The composition and performance of the prepared material are shown in Table 1 (Figure 13). Since the nitrogen atmosphere protection measures described in the present invention are not adopted during the material preparation process, different degrees of oxidation occur in the silicon nitride powder in the raw material, and the thermal conductivity and breakdown field strength of the prepared silicon nitride ceramic material are both obviously reduced, but the bending strength is basically unchanged.
[0052] Comparative Example 2 The specific parameters such as the sintering aid composition ratio, pretreatment process, sintering process, etc. are the same as those in Example 1 (see Table 1 (FIG. 13)), with the difference being that the total amount of sintering aid is increased. The composition and performance of the prepared material are shown in Table 2 (FIG. 14). Since the content of sintering aid is relatively high, the content of grain boundary phase with low thermal conductivity characteristics formed by the sintering aid is relatively high, and the thermal conductivity and breakdown field strength of the prepared silicon nitride ceramic material are both obviously reduced, but the bending strength is basically unchanged.
[0053] Comparative Example 3 The specific parameters such as raw material composition, sintering aid type and total amount, pretreatment process, sintering process, etc. are the same as those in Example 1 (see Table 1 (Figure 13)), except for the composition of the sintering aid (Y2O3:MgO=1.2:4.0). The composition and performance of the prepared material are shown in Table 2 (Figure 14). Because the ratio of MgO in the sintering aid is relatively high, the liquid phase eutectic temperature formed by the sintering aid is relatively low, and volatilization at high temperatures is serious, and the thermal conductivity and breakdown field strength of the prepared silicon nitride ceramic material are both obviously reduced.
[0054] Comparative Example 4 The specific parameters such as the raw material composition, the type and total amount of sintering aids, the pretreatment process, and the sintering process are the same as those in Example 1 (see Table 1 (FIG. 13)), except for the composition of the sintering aids (Y2O3:MgO=1.3:2.0). The composition and performance of the produced material are shown in Table 2 (FIG. 14). Because the ratio of MgO in the sintering aids is relatively low, the liquid phase eutectic temperature formed by the sintering aids is relatively high, and the effect of material densification is relatively poor, so that the thermal conductivity and breakdown field strength of the produced silicon nitride ceramic material are both significantly reduced.
[0055] Comparative Example 5 The specific parameters such as raw material blending, sintering aid composition, pretreatment process, etc. are the same as those in Example 1 (see Table 1 (FIG. 13)), and the process is similar to that in Example 1, with the difference being that the sintering process is a one-step sintering process. The composition and performance of the prepared material are shown in Table 2 (FIG. 14). Since the low-temperature heat treatment process was not included, serious MgO volatilization occurred before the material was fully densified, and the densification effect of the material was relatively poor, and the thermal conductivity and breakdown field strength of the prepared silicon nitride ceramic material were both significantly reduced.
[0056] Comparative Example 6 The specific parameters of the raw material formulation, sintering aid composition, pretreatment process, sintering process, etc. are the same as those of Example 1 (see Table 1 (FIG. 13)), and the process is the same as that of Example 1, except that the temperature of the low-temperature heat treatment is relatively low. The composition and performance of the prepared material are shown in Table 2 (FIG. 14). Because the temperature of the low-temperature heat treatment is relatively low, the densification effect of the material is relatively poor, and both the thermal conductivity and breakdown field strength of the prepared silicon nitride ceramic material are obviously reduced.
[0057] Comparative Examples 7 to 8 Specific parameters such as raw material blending, sintering aid composition, pretreatment process, sintering process, etc. are the same as those in Example 8 (see Table 1 (FIG. 13)), and the process is the same as that in Example 8, with the difference being that the nitriding temperature is relatively low (Comparative Example 7) or relatively high (Comparative Example 8). The composition and performance of the prepared material are shown in Table 2 (FIG. 14). Because the nitriding temperature was relatively low (Comparative Example 7) or relatively high (Comparative Example 8), the Si powder nitriding process in the material was insufficient (Comparative Example 7) or some silicification occurred (Comparative Example 8), and the mechanical, thermal, and electrical performance of the prepared silicon nitride ceramic material were all obviously reduced.
[0058] Example 12 Preparation of solder foil strips (1) Ag powder (average particle size 8μm, oxygen content 0.01%), Cu powder (average particle size 6μm, oxygen content 0.01%) and Ti powder (average particle size 2μm, oxygen content 0.1%) were weighed in a mass ratio of 63:35:2 and placed in a ball mill tank lined with polyurethane. 0.2% oleic acid, 0.5% PEG, 2% PVA, 1% DEP, 200% silicon nitride polishing balls and 110% anhydrous ethanol were added at the same time. After evacuation, a 1atm N2 atmosphere was injected for protection. After ball mill mixing at 100 rpm for 8 hours, a slurry with uniform dispersion and no aggregation was obtained. (2) The prepared slurry was subjected to a vacuum bubble removal treatment for 8 hours at a vacuum level of -0.5 kPa. (3) The slurry after the bubbles were removed was tape-cast in a N2 protective atmosphere, and the thickness of the cast film blank was controlled to 50±10 μm by controlling the height of the scraper. The cast film blank was dried by flowing a hot N2 atmosphere while increasing the temperature. The pressure of the N2 atmosphere was 0.12 MPa, and the temperatures of the N2 atmosphere in the front and back stages were 45°C and 65°C, respectively. (4) The dried cast film blank was cut to a size that matched the silicon nitride ceramic substrate prepared in Example 1 to prepare a raw solder foil piece. As shown in Figure 7, the produced raw active metal solder foil piece had a foil thickness of 50 ± 5 μm, a uniform, smooth and flat surface, excellent flexibility, and could be curled and cut.
[0059] AMB Vacuum Brazing (1) The prepared silicon nitride ceramic substrate, solder foil strip, and oxygen-free copper foil with a thickness of 0.3 mm were assembled to form the laminated component shown in Figure 8. (2) The laminated parts are heated at 650°C for 2 hours in a 0.15 MPa N2 atmosphere. Debinding He made him do so. (3) Debinding The resulting laminated piece was placed in a vacuum brazing furnace and heated for 10 -3 The welding was performed at a vacuum of 10 Pa and at 900°C for 10 minutes. (4) The resulting silicon nitride ceramic substrate with the copper plate was cooled to room temperature in a furnace.
[0060] Figure 9 shows the fabricated silicon nitride ceramic substrate with copper plate, which has high strength, low stress and high stability. Here, the bonding strength (copper foil peel strength) is 15N / mm (detected with reference to GB / T4722-2017 "Test method for hard-coated copper plate for printed circuits") and the flatness of the coated copper plate is 0.2mm. Figures 10 and 11 show the microstructure of the silicon nitride coated copper plate welding area and its component analysis photograph, respectively. As can be seen from these figures, there is a welded area (width corresponds to the width of the solder foil strip) with a width of about 50μm between the silicon nitride ceramic substrate and the copper foil layer, the welded area is mainly composed of Cu (light gray area) and Ag (gray area), where Cu forms the basic continuous phase, Ag forms diffused Ag particles (off-white small particles) and partial area Ag continuous phase (off-white mesh structure), there is an element diffusion reaction transition area with a width of about 100nm between the silicon nitride ceramic and the welded area, where Ti and Si elements react to form a new phase (e.g. Ti5Si3), which ensures the weld strength, and after 200 high-temperature and low-temperature cycle thermal shocks (10 minutes at 300℃ followed by 10 minutes of cooling in a water bath at room temperature is one thermal shock), the fabricated silicon nitride coated copper plate is intact (no extreme high-temperature and low-temperature cycle thermal shock experiments are performed) and there are no visible defects such as microcracks, warping, or cracks (Figure 12).
[0061] Examples 13 to 16 Solder composition, tape casting, copper foil thickness, Debinding Specific parameters such as the vacuum welding process are shown in Table 3 (FIG. 15), and the process procedure is shown in Example 12. The properties of the silicon nitride ceramic substrate with copper plate produced are shown in Table 4 (FIG. 16).
[0062] Examples 17 to 18 Solder composition, tape casting, copper foil thickness, DebindingSpecific parameters such as the vacuum welding process are shown in Table 3 (FIG. 15), and the process is similar to that of Example 12, except that the silicon nitride ceramic material prepared in Example 8 is used as the silicon nitride ceramic substrate, which has a thickness of 0.5 mm. The properties of the prepared silicon nitride ceramic substrate with copper plate are shown in Table 4 (FIG. 16).
[0063] Comparative Examples 9 to 10 Solder composition, tape casting, copper foil thickness, Debinding Specific parameters such as the vacuum welding process are shown in Table 3 (FIG. 15), and the process procedure is based on Example 12. The properties of the silicon nitride ceramic substrate with copper plate are shown in Table 4 (FIG. 16). In the solder composition, the content of the active metal Ti was too low (Comparative Example 9) or too high (Comparative Example 10), so the copper layer peel strength and thermal shock cycle life of the ceramic substrate with copper plate were both significantly reduced (cracks occurred in some of the welded areas of the ceramic substrate and the welded copper foil after 120 and 150 thermal shock cycles, respectively).
[0064] Comparative Examples 11 to 12 Solder composition, tape casting, copper foil thickness, Debinding Specific parameters such as vacuum welding process are shown in Table 3 (FIG. 15), and the process procedure is shown in Example 12. The properties of the silicon nitride ceramic substrate with copper plate are shown in Table 4 (FIG. 16). Because the thickness of the solder foil piece was too small (Comparative Example 11) or too large (Comparative Example 12), the copper layer peel strength of the ceramic substrate with copper plate was partially reduced (Comparative Example 11) or significantly reduced (Comparative Example 12), and the thermal shock cycle life was significantly reduced (after 120 and 100 thermal shock cycles, respectively, crack defects occurred in some welding areas of the ceramic substrate and the welding copper foil).
[0065] Comparative Example 13 Solder composition, tape casting, copper foil thickness, DebindingSpecific parameters such as the vacuum welding process are shown in Table 3 (FIG. 15), and the process procedure is based on Example 12. The properties of the silicon nitride ceramic substrate with copper plate are shown in Table 4 (FIG. 16). Because the thickness of the welded copper foil was too large (2 mm), the copper layer peel strength of the ceramic substrate with copper plate was relatively high, but the thermal stress generated during the thermal shock cycle process was large, and the thermal shock life was significantly reduced (cracks occurred between the ceramic substrate and the copper foil after 80 shock cycles).
[0066] Comparative Example 14 Solder composition, tape casting, copper foil thickness, Debinding The specific parameters of the vacuum welding process are shown in Table 3 (FIG. 15), and the process procedure is based on Example 12. The properties of the silicon nitride ceramic substrate with copper plate are shown in Table 4 (FIG. 16). Because the degree of vacuum in the vacuum welding process is relatively low, the bonding strength between the two is low, and the copper layer peel strength and thermal shock cycle life of the copper plate-attached ceramic substrate are obviously reduced (cracks occurred between the ceramic substrate and the copper foil after 130 shock cycles).
[0067] Comparative Example 15 Solder composition, tape casting, copper foil thickness, Debinding The specific parameters of the vacuum welding process are shown in Table 3 (FIG. 15), and the process procedure is shown in Example 12. The properties of the silicon nitride ceramic substrate with copper plate are shown in Table 4 (FIG. 16). The temperature of the vacuum welding process is too high, obviously exceeding the eutectic temperature of the solder, so the solder melts at high temperature and overflows, and effective welding is not formed between the ceramic substrate and the copper foil, which directly causes cracks.
[0068] Comparative Example 16 Solder composition, tape casting, copper foil thickness, DebindingThe specific parameters of the vacuum welding process are shown in Table 3 (FIG. 15), and the process procedure is based on Example 12. The properties of the silicon nitride ceramic substrate with copper plate are shown in Table 4 (FIG. 16). The temperature of the vacuum welding process is too low and does not reach the eutectic temperature of the solder sufficiently, so the active metal does not diffuse sufficiently to form a good chemical bond, and the copper layer peel strength and thermal shock cycle life of the copper plate-attached ceramic substrate are obviously reduced.
[0069] Comparative Examples 17 to 18 Solder composition, tape casting, copper foil thickness, Debinding Specific parameters for the vacuum welding process are shown in Table 3 (FIG. 15), and the process procedure is based on Example 12. The properties of the silicon nitride ceramic substrate with copper plate are shown in Table 4 (FIG. 16). The heating time at the vacuum welding process temperature was too long (Comparative Example 17) or too short (Comparative Example 18), so the two did not reach an optimal bonding state, and both the copper layer peel strength and thermal shock cycle life of the copper plate-attached ceramic substrate were reduced.
Claims
1. A method for producing a silicon nitride ceramic substrate with a copper plate, comprising the steps of: The silicon nitride ceramic substrate with the copper plate includes a silicon nitride ceramic substrate, copper plates disposed on both the upper and lower sides of the silicon nitride ceramic substrate, and a welding layer disposed between the copper plates and the silicon nitride ceramic substrate; The composition of the silicon nitride ceramic substrate includes a silicon nitride phase and a grain boundary phase, The content of the silicon nitride phase is ≧95 wt %, The grain boundary phase is a mixture containing at least three elements, Y, Mg, and O, and the grain boundary phase has a grain boundary content of ≦5 wt % and a grain boundary phase content of ≧40 vol % by adjusting the grain boundary phase components and contents through a two-stage sintering process; The sintering aid used in the preparation of silicon nitride ceramic substrates is Y. 2 O 3 and MgO, the molar ratio of the two being 1.0-1.4:2.5-2.9; The two-step sintering process includes the steps of first performing a low-temperature heat treatment at 1600-1800°C in a nitrogen atmosphere with an atmospheric pressure of 0.5-10 MPa, and then performing a high-temperature heat treatment at 1800-2000°C; The silicon nitride ceramic substrate has a thickness of 0.2 to 2.0 mm; the composition of the weld layer is AgCuTi, where the mass ratio of Ag:Cu:Ti is x:y:z, where x=0.60-0.65, y=0.33-0.37, z=0.01-0.04, and x+y+z=1; The thickness of the weld layer is 20 to 60 microns; The thickness of the copper plate is 0.1 to 1.5 mm; According to the structure of the silicon nitride ceramic substrate with the copper plate, the copper plate, the solder foil piece formed as a welding layer, and the silicon nitride ceramic substrate are laminated, and the binder is removed in a protective atmosphere, and then the resulting mixture is vacuum-welded under conditions of keeping the temperature at 860 to 920°C for 5 to 20 minutes to obtain the silicon nitride ceramic substrate with the copper plate.
1. A method for producing a silicon nitride ceramic substrate with a copper plate, comprising:
2. The debinding parameters are: 2 2. The method for producing a silicon nitride ceramic substrate with a copper plate according to claim 1, wherein the atmospheric pressure is 0.1 to 0.2 MPa, the treatment temperature is 500 to 800° C., and the treatment time is 1 to 3 hours.
3. The process for producing the solder foil piece is as follows: (1) mixing silver powder, copper powder, titanium powder, an organic solvent and an adhesive in a protective atmosphere to obtain a mixed slurry; 2. The method for producing a silicon nitride ceramic substrate with a copper plate according to claim 1, further comprising the step (2) of tape-casting and drying the obtained slurry in a protective atmosphere to obtain a solder foil piece.
4. The silver powder has an average particle size of 5 to 20 μm and an oxygen content of 0.05% or less, The copper powder has an average particle size of 5 to 20 μm and an oxygen content of 0.05% or less, The titanium powder has an average particle size of 1 to 5 μm and an oxygen content of 0.2% or less, 4. The method for producing a silicon nitride ceramic substrate with a copper plate according to claim 3, wherein the protective atmosphere is a nitrogen atmosphere.
5. Temperature rises due to flow heat N 2 Dry the cast film fabric using a heat N atmosphere. 2 4. The method for producing a silicon nitride ceramic substrate with a copper plate according to claim 3, wherein the temperature range of the atmosphere is 40 to 85° C., and the pressure of the atmosphere is 0.1 to 0.2 MPa.
Citation Information
Patent Citations
High-thermal-conductivity silicon nitride ceramic copper-clad plate and manufacturing method thereof
CN104409425A
Densified silicon nitride ceramic material and preparation method thereof
CN108383532A
High-heat-conductivity silicon nitride ceramic and preparation method thereof
CN108585881A
Manufacturing method of high thermoconductivity high trength silicon nitride ceramic
CN1597614A
Silicon nitride powder, silicon nitride sintered body and circuit substrate, and production method for said silicon nitride powder
EP3156366A1